2009
DOI: 10.2478/v10129-010-0006-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of AFLP molecular markers for estimating genetic similarity of alfalfa (Medicago sativa L. Sl.)

Abstract: Use of AFLP molecular markers for estimating genetic similarity of alfalfa (Medicago sativaL. Sl.)The aim of study was to determine genetic similarity among sixteen alfalfa populations using the AFLP technique. Plant material was selected considering the high genotypic variability. It included populations of different origin: native forms of alfalfa (secondary ecotypes), inbred lines, single hybrids, synthetic populations, varieties and mutants. Analysis was carried out using 10 combinations of primers. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The latter primer was previously used in studies assessing genetic diversity of alfalfa populations and clover species. For alfalfa populations, this primer combination produced the highest mean number of polymorphic fragments (29.9) per population, which was considered relatively low compared to the results of other studies in the same or related species according to Dobrzycka et al (2009). In addition, for clover species, this primer combination amplified 52 bands across four studied populations, which was the lowest number among the four primers used (Bennett and Mathews, 2003).…”
Section: Molecular Characterizationmentioning
confidence: 62%
“…The latter primer was previously used in studies assessing genetic diversity of alfalfa populations and clover species. For alfalfa populations, this primer combination produced the highest mean number of polymorphic fragments (29.9) per population, which was considered relatively low compared to the results of other studies in the same or related species according to Dobrzycka et al (2009). In addition, for clover species, this primer combination amplified 52 bands across four studied populations, which was the lowest number among the four primers used (Bennett and Mathews, 2003).…”
Section: Molecular Characterizationmentioning
confidence: 62%
“…This technique is a highly reproducible method with low error rates ( Jones et al 1997;Powell et al 1996). Amplified fragment length polymorphism markers have been widely used in many plant species to construct genetic maps, to study genetic diversity phylogenic relations and crop evolution, to evaluate germplasm, and to reveal differences between varieties and genotypes (Lübberstedt et al, 2000;Lombard and Delourme, 2001;Hartings et al, 2008;Pawłowicz et al, 2008;Dobrzycka et al, 2009;Bocianowski et al, 2011;Kozak et al, 2011;Liersch et al, 2013;Würschum et al, 2013). Lombard et al (2000), Negi et al (2004), and Faltusová et al (2011) reported that AFLP markers demonstrated the high efficiency of the AFLP technique for genome analysis in Brassica.…”
Section: Assessment Of Genetic Relationships In Breedingmentioning
confidence: 99%